Adolescent acne: association to sex, puberty, testosterone and dihydrotestosterone - Nanna E Jakobsen; Jørgen Holm Petersen; Lise Aksglaede; Casper P Hagen; Alexander S Busch; Trine Holm Johannsen; Hanne Frederiksen; Anders Juul; Stine A Holmboe (Endocrine Connections)
The manifestation of acne in adolescents coincides with the emergence of other androgen-dependent characteristics of puberty such as sweat odor and pubic hair. Yet, little is known about the associations with circulating levels of androgens. Thus, the objective was to study the prevalence of acne in healthy children and adolescents according to sex, age, pubertal stage and concentrations of testosterone and dihydrotestosterone (DHT) quantified by LC-MS/MS. This is a secondary analysis of a larger study on puberty. Data included a combined cross-sectional and longitudinal population-based cohort study, including 1,609 participants from public schools (aged 5.6–23.4) who were assessed for acne. Of these, 222 participants were examined every 6 months for 8 years. In a nested cohort of the cross-sectional population (n = 1,009), concentrations of testosterone and DHT were measured. To determine age at onset of acne, probit analyses were performed, integrating left-, right- and interval-censored data to estimate the mean age at which acne was recorded. In boys, acne occurred at a mean age of 15.0 years (95% CI: 14.7–15.3) based on probit analyses, whereas such analyses could not be performed in girls due to insufficient numbers of girls with acne. Acne was observed in boys in Tanner stages G4 (44%) and G5 (83%) and was less frequent in girls in stages B4 (15%) and B5 (12%). DHT was significantly higher in boys and girls with current acne compared to adolescents without. In conclusion, the prevalence of acne was 85% in late pubertal boys and 15% in late pubertal girls. DHT concentrations were higher in adolescents of both sexes presenting with acne than in those without.